PENGARUH DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DENGAN ETHICAL WORK CLIMATE SEBAGAI VARIABEL MODERASI PADA BIRO UMUM DAN PENGADAAN KEMENTERIAN PERTANIAN RI - Nirastania Isnaeni (2022)
This research is a quantitative study that aims to find out and prove the influence given by independent variables including work discipline and competence to dependent variables, namely employee performance with ethical work climate as a moderation variable in the General Bureau and Procurement of the Ministry of Agriculture. The population on the study object amounted to 220 employees who then sampled as many as 70 respondents using simple random side with the formula Slovin. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis with Partial Least Square (PLS) 3.3.5 version. The results showed that work discipline and competency variables partially had a positive and significant influence on employee performance. Work discipline variables moderated by ethical work climate do not have an influence and are not significant but still have a positive influence, while the competency variables moderated by ethical work climate do not have an influence and are not significant and have a negative influence.